2022
DOI: 10.11591/ijpeds.v13.i1.pp330-339
|View full text |Cite
|
Sign up to set email alerts
|

Maximum resolution of switched capacitor converter: a graphical approach

Abstract: The efficiency of a switched capacitor converter can be represented as the ratio of the output voltage to open-circuit voltage. Switched capacitor converters with adjustable gain are designed with multiple no-load voltages to obtain higher efficiency over the voltage control range. This paper aims to realize the maximum resolution of a switched capacitor converter. A graphical representation of the output voltages formation has been proposed. The voltage composition diagram reveals a switching pattern of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…It has also the minimum total capacitor voltage ratings. The multiphase cycle converter [16], however, provides the maximum number of voltage steps at the expense of large number of series switches in the current path.…”
Section: Discussion Of the Voltage Regulation And Efficiency Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also the minimum total capacitor voltage ratings. The multiphase cycle converter [16], however, provides the maximum number of voltage steps at the expense of large number of series switches in the current path.…”
Section: Discussion Of the Voltage Regulation And Efficiency Resultsmentioning
confidence: 99%
“…One approach to achieve voltage regulation efficiently is based on designing a converter with multiple open-circuit voltages. In the design described in [16], it is shown that the four-capacitor converter can provide up to 21 no-load voltages in the step-down SCC. The implementation of this concept is based on establishing multiple circuit configurations (phases) within the switching cycle which requires full flexibility in the connection of capacitors.…”
Section: Object and Hypothesis Of The Studymentioning
confidence: 99%
“…The selection of capacitors as filters must meet the criteria. The adjustable gain converter switching capacitor is designed with multiple no-load voltages for higher efficiency over the voltage control range [44]. That is, the working voltage must be higher than the supply voltage and the capacitance value.…”
Section: Figure 1 Power Supply Block Diagrammentioning
confidence: 99%